BENIGN CYSTIC OVARIAN TERATOMA IN A CROSS BRED CATTLE - Kannan, Kavitha; I, Poornachandhar; M, Thangapandiyan; Sarath, (The Indian Journal of Animal Reproduction, 2020)
The present study reports a case of benign cystic ovarian teratoma in a cross bred cow. A round mass of size5×5.5×6 cm was found in the right ovary. The mass was firmly encapsulated with cartilaginous tissue and its crosssection revealed tufts of hair matted in thick, dried, yellow sebaceous material. The histopathological investigation ofthe massconfirmed it as benign cystic teratoma. The teratoma was lined by well-differentiated stratifiedsquamouskeratinized epithelium with scattered areas ofhair follicles andsebaceous glands.
Keywords: Cow; Cystic Ovaries; Histopathology; Teratoma